Electrospun nanofibers as a wound dressing for treating diabetic foot ulcer - Yan Liu; Shiya Zhou; Yanlin Gao; Yinglei Zhai (Elsevier, 2019)
Abstracts: Diabetes is one of the most prevalent diseases in the world with high-mortality and complex complications including diabetic foot ulcer (DFU). It has been reported that the difficulties in repairing the wound related to DFU has much relationship with the wound infection, change of inflammatory responses, lack of extracellular matrix (ECM), and the failure of angiogenesis. Following the development of medical materials and pharmaceutical technology, nanofibers has been developed by electrospinning with huge porosity, excellent humidity absorption, a better oxygen exchange rate, and some antibacterial activities. That is to say, as a potential material, nanofibers must be a wonderful candidate for the DFU treatment with so many benefits. Careful selection of polymers from natural resource and synthetic resource can widen the nanofibrous application. Popular methods applied for the nanofibrous fabrication consist of uniaxial electrospinning and coaxial electrospinning. Furthermore, nanofibers loading chemical, biochemical active pharmaceutical ingredient (API) or even stem cells can be wonderful dosage forms for the treatment of DFU. This review summarizes the present techniques applied in the fabrication of nanofibrous dressing (ND) that utilizes a variety of materials and active agents to offer a better health care for the patients suffering from DFU. Keywords: Nanofibers, Nanofibrous dressing, Diabetic foot ulcer, Uniaxial electrospinning, Coaxial electrospinning